A Practical Study On Accurate Delay Measurement - (:unkn) unknown (IEEE, 2020)
The amount of applications that require high bandwidth and low latency, such as video, audio, teleconferencing, is increasing more than ever. The use of such applications by the end user has also increased exponentially in the last 20 years and reached its peak in the 2020 pandemic period. In such applications, service providers had to reduce the quality of their services during the pandemic due to the inability to provide the desired bandwidth and delay. Therefore, to provide services in desired quality, especially for the time critical and interactive applications, it is very important to measure the delay precisely and accurately in order to determine the changes and anomalies occurring in delay and take precautions afterwards. This paper presents the methods and approaches developed for precise and accurate delay measurement and to determine actual state of the network more accurately.
Keywords: delay; video streaming; latency